2015
DOI: 10.3171/2015.2.peds14533
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of routine use of recombinant human bone morphogenetic protein–2 in occipitocervical and atlantoaxial fusions of the pediatric spine: a minimum of 12 months' follow-up with computed tomography

Abstract: OBJECT The purpose of this study focusing on fusion rate was to determine the efficacy of recombinant human bone morphogenetic protein–2 (rhBMP-2) use in posterior instrumented fusions of the craniocervical junction in the pediatric population. The authors previously reported the short-term (mean follow-up 11 months) safety and efficacy of rhBMP-2 use in the pediatric age group. The present study reports on their long-term results (minimum of 12 months' follow-up) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The safety and efficacy of BMP has been documented in adult and pediatric case reports and case series. 64, [130][131][132] Reported complications of BMP include seroma formation, softtissue swelling, delayed wound healing, and heterotopic bone formation. The long-term effects of BMP, such as oncogenesis, are unknown.…”
Section: Biomaterialsmentioning
confidence: 99%
“…The safety and efficacy of BMP has been documented in adult and pediatric case reports and case series. 64, [130][131][132] Reported complications of BMP include seroma formation, softtissue swelling, delayed wound healing, and heterotopic bone formation. The long-term effects of BMP, such as oncogenesis, are unknown.…”
Section: Biomaterialsmentioning
confidence: 99%
“…Normative data to establish the degree of allowable motion over a fused segment for definitive determination of fusion is lacking. 28 A study by Sayama et al 7 includes 34 pediatric cases of occipitocervical or atlantoaxial fusion augmented with rhBMP-2. Fusion was determined by postoperative CT > 12 mo after surgery as interpreted by a neuroradiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reported high rates of fusion, our results, combined with those of Sayama and Sivakumar suggest that, in a generalized population, the rate may be lower than expected. 7,8 Sayama et al 7 reported a fusion rate of 89.2% for pediatric patients (10-17 yr) undergoing occipitocervical or atlantoaxial fusion with rhBMP-2 with >12 mo follow-up using CT imaging. Mazur et al 29 reported a 15.7% failure rate requiring revision surgery in 107 patients (1.2-17.9 yr) undergoing occipitocervical fusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do cover this topic in a series of previously published studies. 10,21,31,32 Furthermore, written informed consent was obtained from the patient or legal guardian for off-label use of bone morphogenetic protein as described above.…”
Section: Surgical Proceduresmentioning
confidence: 99%